(3COhGQ GdCfhGQ eOi GdOghQ hGdGchGQs - (3jMji Hf eMeO Hf CHj GdTcQ, eMjj GdOjf, CHh GdaJM, hjYQa HGdMcje GdeZQHj , GHf CHj GdoqTrcQ , J fMh (B680 (3g`s ((3CHh GdaVd Hf Ydi GdCUa s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOY GdhLhO hCaGV GdLhO bO hVYJ GdRjM HYO JMQjQ efGRd GdCLQGe GdYdhjI GdHGH GdChd ai eHGOF GdJhGQjN s
(3BNQgG (B:s
(3YhO GdTeS Edi ehVYgG GdCUdi hPdc HYO JeGe SfI TeSjI hebOGQgG HMSH CUhdfG ef GdReGf aJNJeg HMeO Gddg s
(3aQZ GdeDda ef cJGHg SfI (B674s
(3GdLOGhd HNW eMeO Hf gdGds
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN YHO GdQMef Hf YHO GdYRjR GdRGed GdNGUI HYfjRIs
Keywords: (3Gdadcs